Peran Optimisme, Kebersyukuran, dan Harapan terhadap Kesejahteraan Psikologis pada Mahasiswa Tingkat Akhir Universitas Muhammadiyah Surakarta - Salsabila, Alifia Rahma; Asyanti, Setia (Jurnal Online Psikogenesis, 2023)
Some final year students often have difficulty completing their studies, which ultimately results in feelings of dissatisfaction and unhappiness. This shows that psychological well-being has not been achieved. This research aims to test whether optimism, gratitude, hope have a simultaneous role in the psychological well-being of final year students. This research used a quantitative approach involving 216 students at Muhammadiyah University of Surakarta who were working on their thesis and aged between 21-23 years. This research used an optimism scale (α = 0.813), a gratitude scale (α = 0.788), a hope scale (α = 0.850), a psychological well-being scale (α = 0.894) which were distributed via Google form. The analysis in this study used multiple linear regression using SPSS statistics 21.0. The results show that the role of optimism, gratitude and hope together on the psychological well-being of final year students is 73%. Hope has the largest contribution, namely 46.1%, followed by optimism, namely 22%. Thus, to improve the psychological well-being of final year students, universities need to carry out activities that increase hope and optimism in final year students.